(untitled) (Nigerian Journal of Health Sciences, 2024)
Introduction: The specialty preferences of medical undergraduates may reflect the pattern of distribution of specialist workforce in the health care system of a country in the future. These choices may also have implications in the maintenance of balance in the availability and demand for specialists in the health care system of the country in the future. Furthermore, the information may also assist in curriculum development and reviews as well as in medical education planning. Objectives: The aim of the study is to determine the likely area of specialization of final year medical students in Obafemi Awolowo University, Ile-Ife, Nigeria, and the likely factors influencing the choice of area of specialization. Methods: This was a cross sectional study involving final year medical students of Obafemi Awolowo University, Ile Ife who were willing to participate in the study. Online questionnaire was administered to students Information obtained included demography, intention to undergo postgraduate training, specialty choice and factors influencing the choice. Data was analyzed using IBMSPSS version 20. Results: Eighty-six out of 105 responders completed the questionnaires adequately. M: F ratio of approximately 2:1. Their age range was aged 22-40 years with a median age of 25 years. Eighty four percent of the respondents would like to do postgraduate specialization. Most of them preferred clinical specialty. Surgery (33.7%) and internal medicine (20.9%) were their most likely specialty area. About 77.9% of our responders were influenced by personal interests. Conclusion: Eighty-four percent of the final year medical students preferred to specialize. Surgery was their most likely specialty and personal interest was the most important factor influencing this choice.